Maleficent’s Personality Changes in Maleficent - Cindy Cornelia; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
In this study, I analyze Maleficent (2014), the first Disney film to place a previously antagonist character into a protagonist in a new film. In this thesis, I found changes in the personality of Maleficent from good to evil and back to good that caused her to experience anxieties. Therefore, I use Sigmund Freud's psychoanalytic theory of three fundamental elements of the human psyche (id, ego, and superego), anxiety and defense mechanisms. Based on my analysis, I found that Maleficent becomes evil when her id, ego, and superego are unbalanced, and Maleficent can return to being good when her id, ego, and superego are well-balanced. Moreover, Maleficent experiences reality anxiety, neurotic anxiety, and moral anxiety during the process of her personality changes, and she uses defense mechanisms such as aggression, intellectualization, and apathy to overcome her anxieties.